Muscle Fatigue Revisited – Insights From Optically Pumped Magnetometers - Sometti, Davide; Semeia, Lorenzo; Baek, Sangyeob; Chen, Hui; Righetti, Giulia; Dax, Juergen; Kronlage, Cornelius; Kirchgässner, Milena; Romano, Alyssa; Heilos, Johanna; Staber, Deborah; Oppold, Julia; et al. (Frontiers in Physiology, 2021)
So far, surface electromyography (sEMG) has been the method of choice to detect and evaluate muscle fatigue. However, recent advancements in non-cryogenic quantum sensors such as optically-pumped magnetometers (OPMs) enable interesting possibilities to flexibly record biomagnetic signals. Yet, a magnetomyographic investigation of muscular fatigue is still missing. Here, we simultaneously used sEMG (4 surface electrode) and OPM-based magnetomyography (OPM-MMG, 4 sensors) to detect muscle fatigue during a 3x1-min isometric contractions of the left rectus femoris muscle in 7 healthy participants. Both signals exhibited the characteristic spectral compression distinctive for muscle fatigue. OPM-MMG and sEMG slope values, used to quantify the spectral compression of the signals, were positively correlated, displaying similarity between the techniques. Additionally, the analysis of the different components of the magnetic field vector enabled speculations regarding the propagation of the muscle action potentials (MAPs). Altogether these results show the feasibility of the magnetomyographic approach with OPMs and propose a potential alternative to sEMG for the study of muscle fatigue.